2007
DOI: 10.1146/annurev.publhealth.28.021406.144016
|View full text |Cite
|
Sign up to set email alerts
|

Church-Based Health Promotion Interventions: Evidence and Lessons Learned

Abstract: Church-based health promotion (CBHP) interventions can reach broad populations and have great potential for reducing health disparities. From a socioecological perspective, churches and other religious organizations can influence members' behaviors at multiple levels of change. Formative research is essential to determine appropriate strategies and messages for diverse groups and denominations. A collaborative partnership approach utilizing principles of community-based participatory research, and involving ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
799
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 705 publications
(826 citation statements)
references
References 46 publications
21
799
0
6
Order By: Relevance
“…Previous studies have found that congregation-sponsored health programming can be valuable in serving vulnerable groups (Campbell et al 2007;Peterson, Atwood, and Yates 2002;Adamczyk and Felson 2012;Trinitapoli, Ellison, and Boardman 2009). In particular, parental education 17 Evangelical inclinations are also diffusing within a number of Mainline Protestant denominations (Ellingson 2007).…”
Section: Find That Mainlinementioning
confidence: 99%
“…Previous studies have found that congregation-sponsored health programming can be valuable in serving vulnerable groups (Campbell et al 2007;Peterson, Atwood, and Yates 2002;Adamczyk and Felson 2012;Trinitapoli, Ellison, and Boardman 2009). In particular, parental education 17 Evangelical inclinations are also diffusing within a number of Mainline Protestant denominations (Ellingson 2007).…”
Section: Find That Mainlinementioning
confidence: 99%
“…Some interventions have successfully increased physical activity among members of traditionally black churches using the church as a community organization through which to disseminate general (non Bible-based) health information (for an overview, see Campbell et al, 2007). Other faith-based weight loss interventions developed intervention messages that highlighted the connection between one's faith and one's health (e.g., Wilcox et al, 2007).…”
Section: Relevant Literaturementioning
confidence: 99%
“…they work directly with hard-to-reach populations; 2. large numbers of children, youth and adults attend weekly worship services and other related activities; 3. they share a mutual concern with primary care and public health institutions about the issues that impact people's health and access to services; and 4. they have existing resources that can be used to support these lifestyle initiatives. [1][2][3][4][5][6][7][8][9] African American churches in the United States have demonstrated how research and community partnerships are flourishing with effective culturally centred interventions. [7][8][9] Christianity is the dominant religion of Pacific people in New Zealand (NZ).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] African American churches in the United States have demonstrated how research and community partnerships are flourishing with effective culturally centred interventions. [7][8][9] Christianity is the dominant religion of Pacific people in New Zealand (NZ). 10 Churches are a visible and well-attended institution for Pacific people, providing them with a sense of belonging and a social institution to foster and develop their spiritual as well as cultural beliefs, values, and practices.…”
mentioning
confidence: 99%
See 1 more Smart Citation